Youth and Peacebuilding: Policy Implications of Conflict Resolution in Africa - Tope Shola Akinyetun; Kola Bakare; Sarah Olufunmilayo Adedini (Advanced Studies on Socio-Economy Development, 2023)
Promoting sustainable peace is a major concern for world regions, especially one enmeshed in recurring conflict and violence, such as in Africa. Ethnoreligious conflicts, boundary disputes, genocide, resource-based conflicts, and youth restiveness characterize many African nations. This idea has been made intricate by a surge in the youth population, massive unemployment, limited education opportunities, and widespread poverty that makes youth key factors in the generation of conflict in Africa. Despite these challenges, the youth of many African nations have distinguished themselves as agents of peace and conflict resolution. On this premise, this article examines youth as agents of peace and reconciliation in Africa. The paper adopts a thematic approach within a qualitative framework and relies on secondary data from briefs, newspapers, conference papers, government reports, and peer-reviewed journal articles. The paper found that shifting focus from the stereotypical prejudice of youth as agents of conflict to agents of peace is instrumental to unlocking their potential as actors in Africa's peace process and conflict resolution. It was also found that youth promote peace and inclusion through advocacy and civic engagement. They use tools such as music, arts, sports, education, storytelling, and interfaith dialogue to build cohesion, resilience, peace, and trust in various parts of Africa. Resultantly, the article made practical policy recommendations such as the establishment of an African Youth Assembly (AYA), African Youth Parliaments (AYP), Youth Participation Commission (YPC), and Youth Empowerment Commission (YEC) – among others. Keywords: Conflict, Governance, Inclusion, Peacebuilding, Youth